THE EFFECT OF PRENATAL YOGA ON LABOR - Sumarni, Sumarni; Sulastri, Ety; Astuti, Dyah Puji (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: Prenatal yoga affects the strengthening and flexibility of the perineal, vaginal, anal sphincter, and urinary tract muscles and is followed by an increase in pelvic diameter. This affects the delivery process. Routine exercise can facilitate minimal trauma labor and reduce the duration of each phase of labor. The purpose of the study was to determine the effect of prenatal yoga on the type of delivery in third trimester pregnant women in the Karanglewas Community Health Center Banyumas. Research method: This type of research uses a pre-experimental design method using an intact-group comparison design, namely the measurement of the case group and control group in the same sample and not chosen randomly. The subjects of this study were pregnant women in the third trimester aged over 34 weeks with 40 respondents consisting of 20 pregnant women in the case group and 20 pregnant women in the control group. The analytical method in this study uses Chi square. The results showed that the results of the chi-square correlation analysis, obtained a probability value (p) of 0.031 with a significance level of 5% (0.05). Because the value is 0.031 < 0.05, it can be stated that prenatal yoga has a significant effect on the type of delivery in pregnant women and Odd Ratio: 7.364 (CI: 1.337-40.548). The conclusion is that prenatal yoga has an effect of 7,364 times on pregnant women to be able to give birth spontaneously vaginally compared to pregnant women who do not do prenatal yoga.